Ac conductivity of Ca1-xAxCu3Ti4O12 (A=Sr or Ba) with x=0.0 and 0.2 ceramics - Mustafa, Mazni; Wan Yusoff, Wan Mohamad Daud; Talib , Zainal Abidin; Shaari, Abdul Halim; Mohamed Kamari, Halimah; Primus, Walter Charles (Malaysian Solid State Science and Technology Society, 2009)
Colossal dielectric constant materials such CaCu3Ti4O12 (CCTO) have recently received an enormous of attention because of their potential in technological applications due to the formation of internal barrier layer capacitor (IBLC) contains semiconducting grains with insulating grain boundaries. Ca1-xSrxCu3Ti4O12(CSCTO) and Ca1-xBaxCu3Ti4O12 (CBCTO) with x = 0.0 and 0.2 ceramics has been doped on Ca site with strontium or barium was prepared using solid state reaction technique. X-ray diffraction pattern shows single phase with cubic structure. In complex impedance plot for both the ceramics show three semicircular arcs re present the grain, the grain boundary and electrode effect responses and modeled using series network of three parallel RC circuits. Two regions were found in conductiv ity plot due to the grain boundary at low frequencies and the grain at high frequencies. The n value obtained from the fitting at the grain region at high frequency dependent are above 0.6 indicates of electron hopping conduction mechanism among Ti 3+and Ti4+. The activation energy values for CCTO are 0.28 eV and 0.74 eV for grain and grain boundary regions, respectively while for CSCTO the energies is 0.27 eVand 0.71 and for CBCTO is 0.31 eV and 0.59 eV for the grain and grain boundary regions respectively.